2013
DOI: 10.1111/ijs.12016
|View full text |Cite
|
Sign up to set email alerts
|

The Obesity Paradox in Stroke: Lower Mortality and Lower Risk of Readmission for Recurrent Stroke in Obese Stroke Patients

Abstract: Obesity was not only associated with reduced mortality relative to normal weight patients. Compared with normal weight, risk of readmission for recurrent stroke was also lower in obese stroke patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
167
2
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(178 citation statements)
references
References 26 publications
5
167
2
4
Order By: Relevance
“…8,10,[22][23][24] However, recently, the obesity paradox was challenged by a study focusing on cause-specific rather than all-cause mortality and reporting no indication of an obesity paradox among stroke patients, when focusing on strokespecific deaths. 25 In our study, we found that overweight/ obese patients also had lower risk of a severe stroke and poststroke pneumonia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,10,[22][23][24] However, recently, the obesity paradox was challenged by a study focusing on cause-specific rather than all-cause mortality and reporting no indication of an obesity paradox among stroke patients, when focusing on strokespecific deaths. 25 In our study, we found that overweight/ obese patients also had lower risk of a severe stroke and poststroke pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10] In addition, most of the existing studies have not been population based and have often been conducted in specialized units which raise concerns about the generalizability of the findings. There is consequently a need for large-scale studies on unselected patients in order better to comprehend the impact of lifestyle on stroke outcomes, including stroke severity, the risk of important medical complications, and mortality in acute stroke care settings.…”
mentioning
confidence: 99%
“…Severe obesity is widely accepted as a risk factor for increased mortality and morbidity [5,11], but being overweight and having mild obesity may have a paradoxical effect in lowering observed overall mortality, and even in decreasing mortality after certain cardiovascular events, a phenomenon known as the obesity paradox [5,[9][10][11]44]. In addition, obese patients have better than expected surgical outcomes when critically ill [45,46] and during the perioperative period [8,47].…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies suggest better than expected outcomes associated with mild obesity, a phenomenon termed the "obesity paradox" [3][4][5][6][7][8][9][10]. The obesity paradox usually refers to the unexplained decreased overall mortality and decreased mortality from cardiovascular events in otherwise healthy mildly obese patients compared to normal weight patients [7,10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation